2018
DOI: 10.1177/0956462418797873
|View full text |Cite
|
Sign up to set email alerts
|

Atypical development of neurosyphilis mimicking limbic encephalitis

Abstract: A previously healthy 35-year-old man suffering from behavioral and mental deterioration for three months was referred to our facility. On admission, the patient was dysphasic and had tonic-clonic seizures. Neurological examination showed mental confusion, euphoric mood, mania, paranoia, and mild motor dysphasia. Magnetic resonance imaging (MRI) was performed twice but no abnormalities were revealed. His acute confusional state, elevated cerebrospinal fluid (CSF) protein, epileptic seizure and electroencephalog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…[ 18 ] Recently, 2 cases of serologically confirmed neurosyphilis presenting as LE accompanied with anti-NMDAR antibodies were published. [ 19 , 20 ] These cases suggest that antibodies might control the symptoms of neurosyphilis. Nevertheless, cases with negativity for NSAs and onconeural antibodies, including the current one, were also reported.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…[ 18 ] Recently, 2 cases of serologically confirmed neurosyphilis presenting as LE accompanied with anti-NMDAR antibodies were published. [ 19 , 20 ] These cases suggest that antibodies might control the symptoms of neurosyphilis. Nevertheless, cases with negativity for NSAs and onconeural antibodies, including the current one, were also reported.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…In addition, the patient showed steroid-responsiveness, and the MRI findings at relapse were consistent with HSVE-related changes, suggesting that HSVE can trigger the expression of NMDA receptor antibodies ( 8 , 9 ). Neurologists have reported detecting an abnormal intensity on brain MRI scans in the hippocampus and/or temporal lobe in patients with neurosyphilis ( 10 , 11 ). Recently, Beiruti et al reported a neurosyphilis case mimicking limbic encephalitis with anti-NMDA receptor antibody, without MRI abnormalities ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neurologists have reported detecting an abnormal intensity on brain MRI scans in the hippocampus and/or temporal lobe in patients with neurosyphilis ( 10 , 11 ). Recently, Beiruti et al reported a neurosyphilis case mimicking limbic encephalitis with anti-NMDA receptor antibody, without MRI abnormalities ( 10 ). Tsukita et al reported a case of neurosyphilis with limbic encephalitis and anti-GluR antibody ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology is attributed to tumours in 38% of cases of which teratoma is the most common type (8). Anti-NMDAR Ab-mediated encephalitis has also been associated with infective encephalitides, including herpes simplex virus (HSV) encephalitis and cryptococcal meningitis, with neuroinflammation possibly acting as a mechanism triggering anti-NMDAR Ab production (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%